Big boots to fill : the next generation continuing differently - Clinton, Eric; Craig, Justin B; Diaz-Moriana, Vanessa; Faherty, Catherine M. (London : SAGE Publications Ltd, 2017)
This case history describes the challenge facing Carlos Garcia, the third-generation successor of a Spanish family business, as he takes over the reins of Hispalis and prepares to continue the business differently. In two generations, Hispalis has morphed into a global conglomerate, with a portfolio of business ventures in multiple industries and countries. The case history facilitates discussion of business and family issues and is appropriate for beginning-level undergraduate students in the areas of entrepreneurial leadership, family business, strategic management and corporate governance.
Originally published in Clinton, E., Craig, J. B., Diaz-Moriana, V., & Faherty, C. M. (2016) Big boots to fill The next generation continuing differently. The International Journal of Entrepreneurship and Innovation, 17(2), 133139. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Family-owned business enterprises -- Case studies; Strategic planning -- Case studies; Corporate governance -- Case studies